Illocution and Perlocution Indicating Politeness and Impoliteness in The Ron Clark Story - Marvel Fransisko Rolan; Aylanda Hidayati Dwi Nugroho (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
This study investigates the speech acts that are present within Shameika’s polite and impolite utterances as responses to Mr. Clark in the movie “The Ron Clark Story”. It is aimed to understand how the compatibility between illocutionary act and intended perlocutionary effect can indicate the politeness degree in educational settings by students and teacher. This research addresses a gap in the relation between speech act and politeness degree within educational context, particularly focusing on Shameika as a student. The analysis is based on theories by Austin (1962), Short (1997), Brown and Levinson (1978), Culpeper (2011), and Brown and Prieto (2017). The findings reveal that there is a relation between speech act and politeness degree. The illocutionary act of Shameika’s impolite utterances that are directed toward Mr. Clark cannot fulfil Mr. Clark’s intended perlocutionary effect, even when she uses mock impoliteness when their relationship is already close. Meanwhile, the illocutionary act of Shameika’s polite utterances that are directed toward Mr. Clark can fulfil Mr. Clark’s intended perlocutionary effect, even if the polite utterance is not produced voluntarily by Shameika. The study concludes that one of the most effective ways for a student to produce polite utterances toward a teacher is by fulfilling the teacher’s intention.